A Literature Review of The Effect of Work-Life Balance Towards Employee Performance - Putri Fasya, Velicia; Elliv Hidayatul Lailiyah (International Journal of Economics, Business and Innovation Research, 2026)
With Generation Z entering the workforce, they bring a new perspective to their work expectations, prioritizing balance and flexibility in their work. This literature review has the purpose of analyzing any impact from Work-life balance towards performance by employee in companies nowadays. By examining 10 recently empirical studies conducted across various sectors also geographical contexts, this study provides consistent evidence of a true and significantally association between WLB and employee performance. Work–life balance reflects individuals’ capacity to manage work-related demands alongside personal responsibilities and is widely recognized as a key factor in fostering a healthy, productive, and sustainable work environment. These findings confirm that organizations that effectively implement WLB policies are able to boost employee well-being and also boost their quality work. Therefore, work–life balance needs to be prioritized as part of human resource management strategies to support improved employee performance and organizational or company sustainability. This review provides a conceptual contribution to companies and researchers in understanding the necessity of Work–life balance become main aspect for improving employee quality of work.